2012
DOI: 10.1111/j.1743-7563.2012.01564.x
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of BMI‐1 is associated with poor prognosis in cervical cancer

Abstract: The high expression of BMI-1 in cervical cancer is related to tumor progression, lymph node metastasis and HPV infection, suggesting that cervical cancer with excessive BMI-1 expression possesses high metastases potential and that BMI-1 may be a promising biomarker for predicting metastasis in cervical cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 25 publications
3
26
0
Order By: Relevance
“…Consistent with our results, research on ovarian cancer [35], breast cancer [36, 37], clear cell renal cancer [38], laryngeal carcinoma [39], cervical cancer [40], and esophageal adenocarcinoma [41] have reported an association between high Bmi-1 expression and an unfavorable prognosis. It has also been reported that high expression of Bmi-1 in AML cells is associated with an unfavorable prognosis [42].…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with our results, research on ovarian cancer [35], breast cancer [36, 37], clear cell renal cancer [38], laryngeal carcinoma [39], cervical cancer [40], and esophageal adenocarcinoma [41] have reported an association between high Bmi-1 expression and an unfavorable prognosis. It has also been reported that high expression of Bmi-1 in AML cells is associated with an unfavorable prognosis [42].…”
Section: Discussionsupporting
confidence: 92%
“…B lymphoma Mo-MLV insertion region 1 homolog (BMI-1), a member of the polycomb group (PcG), functions as a transcriptional repressor and presents with high expression in many tumors including HCC, indicating a poor prognosis (22,23). BMI-1 has been shown to be an oncogene that regulates cell proliferation and transformation (19).…”
Section: Discussionmentioning
confidence: 99%
“…Bmi1 is overexpressed in various solid cancers (47,48), including CRC (49), where increased Bmi1 expression correlates with poor prognosis (50). Bmi-1 is a regulatory subunit of the polycomb repressor complex 1.…”
Section: Discussionmentioning
confidence: 99%